2005
DOI: 10.3917/reof.092.0043
|View full text |Cite
|
Sign up to set email alerts
|

Doit-on oublier la politique budgétaire ?

Abstract: 4 juin 2004. Les auteurs remercient Francesco Saraceno qui a participé aux travaux ayant abouti à cet article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 60 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…European governments seem to be reluctant to adopt such a rule, despite it being applied in one of them -the UK -, but we have showed that the reasons for its rejection are generally not legitimate. Among these reasons, the textbook drawback associated with higher public expenditures -the crowding out effect -has already been argued to be weak theoretically (see Arestis and Sawyer, 2003;Creel et al, 2004); here, it is argued that empirically, this effect should not be overstated: it does not preclude higher economic growth and in many cases, it is not statistically significant. The null hypothesis assumes common unit root process.…”
Section: Resultsmentioning
confidence: 99%
“…European governments seem to be reluctant to adopt such a rule, despite it being applied in one of them -the UK -, but we have showed that the reasons for its rejection are generally not legitimate. Among these reasons, the textbook drawback associated with higher public expenditures -the crowding out effect -has already been argued to be weak theoretically (see Arestis and Sawyer, 2003;Creel et al, 2004); here, it is argued that empirically, this effect should not be overstated: it does not preclude higher economic growth and in many cases, it is not statistically significant. The null hypothesis assumes common unit root process.…”
Section: Resultsmentioning
confidence: 99%
“…However, the generality of these "non-Keynesian" effects of fiscal policy has been put into question. On the one hand, successful expansionary fiscal contractions have been coupled with other simultaneous events (such as a decrease in interest rates, a depreciation of the exchange rate, episodes of wage moderation, or a decrease in taxes on labour), which should preclude explaining the favourable economic evolution exclusively in terms of the restrictive fiscal policy; see, e.g., Creel et al (2005) or Perotti (2013). On the other hand, recent studies using a novel methodology (namely, identifying changes in fiscal policy motivated by the desire to reduce the budget deficit from historical documents) find that fiscal consolidations have a contractionary effect on economic activity, as expected from standard Keynesian models; see Romer and Romer (2010) and Guajardo et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a cut in the level of public expenditures would have a positive impact on private demand, which would at least partially balance the negative effect of a fiscal retrenchment on activity. This thesis is thus part of the new anti-Keynesian view of public finances (see Creel and al., 2005). However, it does not seem to be confirmed by the data: in the United States, for example, the increase in the real interest rate, in 1980, precedes the public finances worsening whereas the low level of interest rates in the years [2002][2003][2004] goes with a high fiscal deficit.…”
mentioning
confidence: 99%